Production of Transgenic Animals derived from in vitro Fertilized Eggs cryopreserved by Ultrarapid Freezing - Hyun Kim; Changyong Choe; Hwan-Hoo Seong (The Korean Society of Animal Reproduction and Biotechnology, 2015)
Many pronuclear stage eggs were used to generate transgenic mice (Tg) by microinjection. In this study, we used in vitro fertilized mouse eggs, followed by ultrarapid freezing to establish a simple procedure for production of Tg mice. We produced in vitro fertilized mouse eggs and cryopreserved them by ultrarapid freezing method. A total of 139 cryopreserved-thawed pronuclear eggs, of which 101 (72.6%) were survived following microinjection of chicken b-actin promoter-driven firefly improved luciferase cDNA (β-act/luc+) and were transferred into 5 recipients. All recipients became pregnant and gave birth to a total of 15 (14.8%) pups. As a control, same DNA construction (β- act/luc+) was also injected into 450 in vitro fertilized eggs, of which 338 (75.1%) were survived and then were transferred into 14 recipients. Eleven (78%) mice became pregnant and littered a total of 54 (19.1%) pups. Southern blotting analysis of Tg mice indicated that one (1/15, 6.6%) and three (3/54, 5.5%) transgenic mice were production from cryopreserved and in vitro fertilized eggs, respectively. All Tg mice produced from both eggs showed the expression of improved luciferase gene. These results indicated that efficiency of produced of Tg mice from cryopreserved eggs was comparable to that from in vitro fertilized eggs. Furthermore, it is suggested that microinjection of transgene into in vitro fertilized eggs cryopreserved by ultrarapid freezing is an easy and conveniently method for production of Tg mice.